2018
DOI: 10.1001/jamacardio.2018.0095
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Obstructive Sleep Apnea With Atrial Fibrillation and Continuous Positive Airway Pressure Treatment

Abstract: Data from nonrandomized studies of patients with AF suggest that treatment of OSA by continuous positive airway pressure may help to maintain sinus rhythm after electrical cardioversion and improve catheter ablation success rates. Randomized clinical trials are needed to confirm the association between OSA and AF the benefits of treatment of OSA and the need for and cost-effectiveness of routine OSA screening and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
193
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 300 publications
(248 citation statements)
references
References 78 publications
3
193
0
14
Order By: Relevance
“…Lastly, since atrial enlargement has been previously identified as a risk factor for the recurrences, future studies with a large population are needed to assess the efficacy of CPAP on reversal the structural changes of the atrium, as an underlying mechanism reducing the risk for AF recurrence after ablation. Well‐designed RCTs are also required to address the impact and cost‐effectiveness of CPAP and AF recurrence after ablation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, since atrial enlargement has been previously identified as a risk factor for the recurrences, future studies with a large population are needed to assess the efficacy of CPAP on reversal the structural changes of the atrium, as an underlying mechanism reducing the risk for AF recurrence after ablation. Well‐designed RCTs are also required to address the impact and cost‐effectiveness of CPAP and AF recurrence after ablation …”
Section: Discussionmentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is a well‐known, effective therapy for OSA. Several studies have demonstrated favorable effects of CPAP therapy on preventing arrhythmias recurrence, heart rate control in patients with AF, and in decreasing severity and/or frequency of ventricular extrasystoles Although the exact mechanism of CPAP use improves the success of AF treatment remains unclear, it has been suggested to be due to a reduction of the structural and electrical remodeling of the left atrium and oxidative stress, resulting in a lower recurrence rate of AF . Although the association between OSA and AF has been well established, it remains controversial whether patients with OSA carry a higher risk of recurrent AF after successful catheter ablation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that OSA contributes to the development of AF and a number of potential mechanisms have been proposed to explain the association such as intermittent hypoxia, recurrent arousals and increased negative intrathoracic pressure. 23 This can result in increased sympathetic nerve activity and oxidative stress, and possible electrical and mechanical remodelling of both atria and the left ventricle. 23 This is the first study to demonstrate improvement in AHI with long-term restoration of sinus rhythm confirmed with ICMs.…”
Section: Discussionmentioning
confidence: 99%
“…23 This can result in increased sympathetic nerve activity and oxidative stress, and possible electrical and mechanical remodelling of both atria and the left ventricle. 23 This is the first study to demonstrate improvement in AHI with long-term restoration of sinus rhythm confirmed with ICMs. Improving haemodynamic status and cardiac function with long-term restoration of SR could reduce fluid displacement from the lower limbs to the neck region of the body, a key mechanism in the pathogenesis of OSA.…”
Section: Discussionmentioning
confidence: 99%